(untitled) (LACCEI, 2024)
The containment measures adopted by the governments to curb the spread of the pandemic in 2020 affected to a greater or lesser extent the different sectors of global economic activity. In that sense, the objective of this research was to determine how the restrictive measures imposed by the Peruvian government to contain the spread of Covid-19 impacted the financial management of the Savings and Credit Cooperative. A single group linear contrast design was applied, with a transversal, non-experimental approach. The financial statements and complementary information of the entity were analyzed, which allowed to understand the management and behavior of liquidity before (2019) and after such restrictions (2020). The results obtained revealed that the government restrictive measures imposed due to the Covid-19 health crisis did not have a determining influence on its liquidity. Its negative impact is recognized however, the reduction in available funds at the end of the 2020 period can also be explained by other factors, such as inadequate credit granting policies and inefficient collection management, reflected in a high delinquency rate (15%) and a low level of liquidity coverage (23%), which have been present in previous years. It is suggested to deepen the study considering the important role played by these microfinance sector organizations in credit decentralization.